2020
DOI: 10.1302/2046-3758.16.bjo-2020-0060.r1
|View full text |Cite
|
Sign up to set email alerts
|

Providing a paediatric trauma and orthopaedics service during the peak of the COVID-19 pandemic

Abstract: Introduction In response to the COVID-19 pandemic, there was a rapidly implemented restructuring of UK healthcare services. The The Royal National Orthopaedic Hospital, Stanmore, became a central hub for the provision of trauma services for North Central/East London (NCEL) while providing a musculoskeletal tumour service for the south of England, the Midlands, and Wales and an urgent spinal service for London. This study reviews our paediatric practice over this period in order to share our experience and less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“… 129 However, in the study of Iliadis et al patients across different orthopedic subspecialties underwent the surgery without respiratory complications in the early postoperative period. 130 …”
Section: Methodsmentioning
confidence: 99%
“… 129 However, in the study of Iliadis et al patients across different orthopedic subspecialties underwent the surgery without respiratory complications in the early postoperative period. 130 …”
Section: Methodsmentioning
confidence: 99%
“…These preparations for VC provided helpful groundwork for the rapid implementation process. The RNOH does not have an emergency department so was not subject to an immediate surge of patients with COVID-19, although the Trust did establish a new emergency orthopaedic trauma referral pathway enabling acute trusts to free up bed capacity elsewhere in London 5. There was also a strict limit on the type of activity that could take place at the hospital to help to minimise the spread of COVID-19.…”
Section: Success Factorsmentioning
confidence: 99%
“…A recent study has shown that operating on a paediatric population during the peak of COVID-19 did not result in symptomatic spread of COVID-19 in any patient or their households. 4 Despite this, there were still concerns that children may be asymptomatic carriers. 5 , 6 , 7 Furthermore, some hospital institutions restarted elective orthopaedic surgery on green (non-covid) sites during the de-escalation phase and early results show that elective surgery is safe and had high satisfaction rates with adequate resources and appropriate infrastructure.…”
Section: Introductionmentioning
confidence: 99%